2004
DOI: 10.1002/mrd.20076
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor promotes cell proliferation and inhibits progesterone secretion via PKA and MAPK pathways in a human granulosa cell line

Abstract: Hepatocyte growth factor (HGF) is a mesenchymal-derived paracrine factor that acts through a c-met receptor. The activated c-met receptor recruits various signal proteins. We used a steroidogenic human granulosa-like tumor cell line (KGN cells) to analyze the biological function of HGF in human ovary cells. First, we designed a method to analyze local production and action of HGF in the human ovary. Although c-met mRNA is expressed in KGN cells, granulosa lutein, theca, and ovarian stroma cells, we observed HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
2
21
0
1
Order By: Relevance
“…Our data confirm findings by de Mare‐Bredemeijer et al, which showed a higher expression of PTGS1 in L‐MSCs than in BM‐MSCs . Third, HGF, which is known to have antiapoptotic and anti–T cell proliferative properties, was expressed exclusively in L‐MSCs, similar to findings reported previously . HGF transcripts were found in MSCs previously and thought to be responsible for their ability to avoid allorecognition .…”
Section: Discussionsupporting
confidence: 92%
“…Our data confirm findings by de Mare‐Bredemeijer et al, which showed a higher expression of PTGS1 in L‐MSCs than in BM‐MSCs . Third, HGF, which is known to have antiapoptotic and anti–T cell proliferative properties, was expressed exclusively in L‐MSCs, similar to findings reported previously . HGF transcripts were found in MSCs previously and thought to be responsible for their ability to avoid allorecognition .…”
Section: Discussionsupporting
confidence: 92%
“…The MAPK3/1-dependent pathway also has been reported as being involved in the regulation of steroidogenesis in granulosa cells; however, its precise role in this process is controversial. Some studies suggest that activation of MAPK is required for promoting steroidogenesis and steroidogenic gene expression in granulosa cells [36][37][38][39][40][41][42], whereas other studies indicate that activation of MAPK3/1 suppresses granulosa cell steroidogenesis and steroidogenic gene expression [38,[43][44][45]. Notably, most of the previous studies use either human luteinizing granulosa cells derived from patients receiving in vitro fertilization treatment or rat granulosa cells isolated from early antral follicles.…”
Section: Introductionmentioning
confidence: 93%
“…4C). Interestingly, although c-Met activation has been demonstrated to promote proliferation in certain cell types (Wang et al 2003, Taniguchi et al 2004, HGF/SF did not produce any significant change in the growth of either cell type over a period of 7 days (Fig. 4D).…”
Section: Activation Of C-met In Fas-r Cells By Exogenous Ligand Greatmentioning
confidence: 77%